EFL Learners’ Perception on The English Reading Instruction with Non Fiction English Texts: English - Jaya Nur Iman; Nike Angraini (Prodi Tadris Bahasa Inggris, 2023)
The present investigation was about to highlight whether the EFL learners had positive perception or not on English reading instruction with non fiction English texts. A design of experimental research which chiefly focused on the descritpive analysis was utilized. The sample was chosen purposively which it comprised of 17 male students and 15 female students of junior high school in Palembang. 10 question items were accordingly designed as a primary instrument in a close-ended questionnaire. However, there were twenty participants of which consisted of 5 male students and 15 female students filled out the questionnaire based on the time given. The research findings showcased that mostly the participants had positive responses (strongly agree and agree) due to the use of non fiction English text in English reading instruction. Thus, it could be concluded that the there was positive perception on the participants’ reading comprehension with integration of non fiction English text in English reading class.